PUBLIC-PRIVATE PARTNERSHIP - ONE OF THE WAYS TO ENHANCE THE EFFECTIVENESS OF AIR NAVIGATION SERVICES - R. G. Malyshev (Научный вестник МГТУ ГА, 2016)
The article examines existing in different countries legal forms providers for Air Navigation Services. The tendency of transition from state organizations to different form public-private partnership, until fully private enterprises. Based on the positive experience of the world is invited to reform the air navigation system of air traffic services of Russian on a public-private partnership.